The role of embryo movement in the development of the furcula. Issue 3 (6th December 2016) - Pollard, A. S.; Boyd, S.; McGonnell, I. M.; Pitsillides, A. A.
Abstract: The pectoral girdle is a complex structure which varies in its morphology between species. A major component in birds is the furcula, which can be considered equivalent to a fusion of the paired clavicles found in many mammals, and the single interclavicle found in many reptiles. These elements are a remnant of the dermal skeleton and the only intramembranous bones in the trunk. Postnatally, the furcula plays important mechanical roles by stabilising the shoulder joint and acting as a mechanical spring during flight. In line with its mechanical role, previous studies indicate that, unlike many other intramembranous bones, furcula growth during development can be influenced by mechanical stimuli. This study investigated the response of individual aspects of furcula growth to both embryo immobilisation and hypermotility in the embryonic chicken. The impact of altered incubation temperature, which influences embryo motility, on crocodilian interclavicle development was also explored. We employed whole‐mount bone and cartilage staining and 3D imaging by microCT to quantify the impact of rigid paralysis, flaccid paralysis and hypermobility on furcula growth in the chicken, and 3D microCT imaging to quantify the impact of reduced temperature (32–28 °C) and motility on interclavicle growth in the crocodile. This revealed that the growth rates of the clavicular and interclavicular components of the furcula differ during normal development. Total furcula area was reduced by total unloading produced by flaccid paralysis, but not by rigid paralysis which maintains static loading of embryonic bones. This suggests that dynamic loading, which is required for postnatal bone adaptation, is not a requirement for prenatal furcula growth. Embryo hypermotility also had no impact on furcula area or arm length. Furcula 3D shape did, however, differ between groups; this was marked in the interclavicular component of the furcula, the hypocleideum. Hypocleideum length was reduced by both methods of immobilisation, and interclavicle area was reduced in crocodile embryos incubated at 28 °C, which are less motile than embryos incubated at 32 °C. These data suggest that the clavicular and interclavicle components of the avian furcula respond differently to alterations in embryo movement, with the interclavicle requiring both the static and dynamic components of movement‐related loading for normal growth, while static loading preserved most aspects of clavicle growth. Our data suggest that embryo movement, and the mechanical loading this produces, is important in shaping these structures during development to suit their postnatal mechanical roles.